What´s new with the men´s program - USA Gymnastics men´s program (Technique, 2013)
The USA Gymnastics Men's Program introduced a reformatted and reorganized Junior Olympic Age Group Program, beginning with the 2012-13 season. It has been the largest, most involved program change since 1996. The reasons for the changes were to address the tremendous growth in the boy's age group program at the participation level and to improve future international performances of the USA Gymnastics Men's Team. Probably the most recognizable change thai we've made in the Junior Olympic program is to utilize two-divisions - a Junior Olympic division and a Junior Elite division. Athletes and coaches can choose which division they want to pursue, and there is a lot of flexibility to move back and forth between the divisions. The Junior Elite division is eligible to make our Junior National Team. This division will also sels of routines - optional routines and technical sequences. USA gymnastics experienced enough growth and diversity in numbers, especially at the optional levels, that were was a need to provide better peer-to-peer opportunities. Plus, on the elite side, the need to address the international weakness, which is technical gymnastics and where is a need to make sure to fielding teams that can compete at the highest levels. The technical sequences allow for a focused approach to developing gymnastics skills and obviously require a higher love! of work and refinement Internationally, USA Gymnastics is virtually equal with rest of world with difficulty and consistency, so this is the final dimension to be addressed.